Discussing Holistic-Integrative Islamic Science in Higher Education in the Postmodern Era - Shofwan, Arif Muzayin (Journal of Modern Islamic Studies and Civilization, 2025)
The construction of Islamic science constantly changes according to the unavoidable needs of its time. In the era of traditionalism, Islamic science's construction seems more normative and theological. In the era of modernism, the construction of Islamic science appears to be more empirical and sociological. Unlike the era of postmodernism, the construction of Islamic science is more holistic and integrative. With a qualitative descriptive approach, this writing aims to examine the construction of Islamic science that is holistic-integrative in higher education in the current era of postmodernism. This writing method uses library studies by reviewing various literature following the discussion. This writing produces several findings as follows. First, the era of postmodernism is an era of searching for the correct form (model) by using a "combined model" or "Islamization of science model." Second, in the era of globalization, it is impossible to avoid the development of technology and science, so efforts are needed to integrate and combine religious sciences and general sciences; further studies must continue to be carried out. With these various further studies, the right analytical tool will be found in the era of postmodernism like today.